Smart Edge Device Utilizing Power Line Communication for Energy Management and Control of Electrical Appliances - L. N. Sastry Varanasi; Ankamma Rao Jonnalagadda; Sri Phani Krishna Karri (IEEE Access, 2024)
The integration of intelligent systems in various industries has led to notable advancements in energy resource utilization. Power Line Communication (PLC) is widely used in the power industry for transmitting telemetry, speech, and protective tripping commands. While Wi-Fi has limitations in remote control and monitoring applications due to cost and power consumption, Wireless Sensor Networks (WSNs) face challenges like transmission errors and data losses. Developing a scalable WSN architecture is crucial, especially in the presence of excessive network coverage or non-line-of-sight situations. Challenges persist despite efforts to enhance WSN connectivity, and conflicts with wireless local area networks (WLANs) in the 2.4 GHz ISM band lead to issues like packet losses and interference. To address these issues, the proposal suggests integrating WSN with PLC technology to create a resilient utility network. The research introduces a Master-Slave system using frequency-shift keying (FSK) based PLC modules for effective management and supervision of the intelligent utility network, with scalability for diverse industrial intelligence applications.